2022
DOI: 10.3390/ijms232012556
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence in Combination with Organic Photosensitizers: Beyond the Light Penetration Depth Limit of Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a promising noninvasive medical technology that has been approved for the treatment of a variety of diseases, including bacterial and fungal infections, skin diseases, and several types of cancer. In recent decades, many photosensitizers have been developed and applied in PDT. However, PDT is still limited by light penetration depth, although many near-infrared photosensitizers have emerged. The chemiluminescence-mediated PDT (CL-PDT) system has recently received attention because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 67 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…66,67,114 Because light penetration is limited in the visible range, these drugs are used for the treatment of superficial skin diseases with therapeutic depths of <2 mm; AK, for example, is usually <300 μm deep. 115,116 Patients with FST IV-VI are at a greater risk of epidermal injury and hyperpigmentation or hypopigmentation due to PDT than those with light skin due to laser energy absorption by melanin at the wavelengths used for treatment. 20 Accurate determination of the individual's skin properties and the associated absorption and scattering coefficients is required to reduce adverse effects by personalizing treatment regimens including reducing the doses of light, the strength of the photosensitive drug, and the incubation time of the drug on the skin.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…66,67,114 Because light penetration is limited in the visible range, these drugs are used for the treatment of superficial skin diseases with therapeutic depths of <2 mm; AK, for example, is usually <300 μm deep. 115,116 Patients with FST IV-VI are at a greater risk of epidermal injury and hyperpigmentation or hypopigmentation due to PDT than those with light skin due to laser energy absorption by melanin at the wavelengths used for treatment. 20 Accurate determination of the individual's skin properties and the associated absorption and scattering coefficients is required to reduce adverse effects by personalizing treatment regimens including reducing the doses of light, the strength of the photosensitive drug, and the incubation time of the drug on the skin.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…These features make CL a promising excitation source for various bioapplications such as drug delivery, [23] bioimaging, [24] and photodynamic therapy. [25,26] Despite its widespread use in biological systems, the use of CL as a light source for photopolymerization is still in its infancy. In 2018, the pioneering work of using CL as a physical light source for free radical photopolymerization of various (methyl) acrylates was accomplished using a bisacylgermane compound as a highly efficient photoinitiator.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists found that the chemical energy could replace the light energy and be utilized as one new excited source. The chemiluminescence resonance energy transfer (CRET) method could activate the PSs in situ without light irradiation, overcoming the limitation of tissue penetration depth in PDT. Specially, chemical energy was generated through the reaction between hydrogen peroxide (H 2 O 2 ) and peroxyoxalate derivatives, while the energy could be absorbed by surrounding PSs via the CRET pathway to directly generate 1 O 2 . For example, bis­[2,4,5-trichloro-6 (pentyloxycar-bonyl) phenyl] oxalate (CPPO) could react with H 2 O 2 to realize the CRET-induced PDT. , However, it is worthy to note that some barriers might influence the CRET-induced PDT outcomes. First, the π–π stacking interactions of PSs always decrease the 1 O 2 yield. In addition, although the H 2 O 2 amount was overexpressed in tumor tissue (0.1–1 mM), it is still insufficient for the production of satisfactory chemical energy. Finally, the biodegradation was also necessary to be considered in the design of nanosystems.…”
Section: Introductionmentioning
confidence: 99%